Identification of Air Bacteria Using Gram Style Methods in The Integrated Laboratory of Bina Mandiri University Gorontalo - Erfan Lainjong (Westscience Press, 2024)
Microbiology is the study of microorganisms which cannot be seen with the naked eye to examine what is contained in microorganisms. To see microorganisms, it is necessary to have gram stain which is one of the most widely used procedures to characterize many bacteria. This study aims to understand the chemical and theoretical basis for the differential staining procedure as well as the procedure for differentiating between the two main groups of bacteria namely gram positive and gram negative. The method used in this research is the experimental method. The experimental method is a method used in laboratory research. The purpose of this experimental method is to determine the consequences of a treatment given deliberately by the researcher. In addition, a qualitative descriptive approach was used to provide an overview of airborne bacteria by using the gram stain method. The results showed that samples of NA media in airborne bacteria were carried out using a microscope at 10x magnification, which aims to see the color of the bacteria, in the gram staining experiment that has been carried out produces a purple color. This shows that these bacteria are included in the gram-positive bacteria group, as well as the results of the type of bacteria obtained in the gram stain experiment, namely E. coli bacteria which has aform monobacillus.